The cosmic axion spin precession experiment (CASPEr): a dark-matter search with nuclear magnetic resonance. (15th December 2017) - Garcon, Antoine; Aybas, Deniz; Blanchard, John W; Centers, Gary; Figueroa, Nataniel L; Graham, Peter W; Kimball, Derek F Jackson; Rajendran, Surjeet; Sendra, Marina Gil; Sushkov, Alexander O; Trahms, Lutz; Wang, Tao; et al.
Abstract: The cosmic axion spin precession experiment (CASPEr) is a nuclear magnetic resonance experiment (NMR) seeking to detect axion and axion-like particles which could make up the dark matter present in the Universe. We review the predicted couplings of axions and axion-like particles with baryonic matter that enable their detection via NMR. We then describe two measurement schemes being implemented in CASPEr. The first method, presented in the original CASPEr proposal, consists of a resonant search via continuous-wave NMR spectroscopy. This method offers the highest sensitivity for frequencies ranging from a few Hz to hundreds of MHz, corresponding to masses m a ∼ 10 − 14 – 10 − 6 eV. Sub-Hz frequencies are typically difficult to probe with NMR due to the diminishing sensitivity of magnetometers in this region. To circumvent this limitation, we suggest new detection and data processing modalities. We describe a non-resonant frequency-modulation detection scheme, enabling searches from mHz to Hz frequencies ( m a ∼ 10 − 17 – 10 − 14 eV), extending the detection bandwidth by three decades.